Association of Low Lysosomal Enzymes Activity With Brain Arterial Dilatation: A Pilot Study. Issue 8 (August 2018) - Shah, Harsh; Liong, Christopher; Levy, Oren A.; Waters, Cheryl; Fahn, Stanley; Marder, Karen; Kang, Un J.; Wolf, Pavlina; Oliva, Petra; Zhang, Kate; Alcalay, Roy N.; Gutierrez, Jose
Abstract : Background and Purpose—: Absent or diminished α-galactosidase A (GLA) and acid α-glucosidase (GAA) enzyme activity are core features of Fabry and Pompe disease, respectively. Patients with Fabry or Pompe disease may have dilated intracranial arteries but whether lower GLA or GAA enzyme activity relates to brain arterial dilatation in other populations is unknown. Methods—: Participants included Parkinson disease patients and nonblood-related controls, whose GLA and GAA enzymatic activities were measured in dried blood spots. Independent readers measured the axial arterial diameter of the ascending portion of the cavernous internal carotid arteries and the most proximal segment of the basilar artery in T2 black voids. Linear regression models were built to investigate the relationship between brain arterial diameters and lysosomal enzymatic activities. Results—: The cohort included 107 participants (mean age, 66.5±10.3; 67% men). In an adjusted linear regression model, lower GLA activity was associated with larger brain arterial diameters (B=0.50±0.23, P =0.03). The strength of association was the greatest for the basilar artery diameter (B=0.80±0.33, P =0.02). Similarly, lower GAA activity was associated with an increased basilar arterial diameter (B=0.73±0.35, P =0.04). Conclusions—: Lower GLA and GAA enzymatic activities were associated with larger brain arterial diameters, particularly the basilar artery diameter. Lower lysosomal enzymatic function in patients without Fabry or Pompe disease may play a role in brain arterial dilatation. Abstract : Supplemental Digital Content is available in the text.